Floristic Diversity and Medicinal importance of South Vagaikulam Region Tirunelveli, Tamil Nadu, South India - Maharajan M, Janakiraman NFloristic Diversity and Medicinal importance of South Vagaikulam, Johnson M (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The present study was aimed to explore the plant diversity wealth of South Vagaikulam village, which is yet to be botanised to make the flora of Tirunelveli complete. The result of plant diversity of South Vagaikulam shrub jungles includes 133 species of flowering plants, 115 genera belonging to 49 families. Among the 133 species, 126 species belongs to dicotyledons and 7 species belongs to monocotyledons. The most dominant family in the present study area is Asteraceae with 12 species (21%). Next to that, Fabaceae and Euphorbiaceae comprises 10 species (19%), Amaranthaceae includes 9 species (17%), Lamiaceae contains 8 species (15%) and Verbenaceae embraces 5 species (9%). In addition to the floristic study, the present study enumerated the medicinally important plants in the shrub jungles which are used to cure various diseases.